Images of Jesus: How Jesus is Perceived and Portrayed in Non-European Cultures - Athappilly, Sebastian (Journal of Dharma, 1992)
A. Wessels, Images of Jesus. How Jesus is Perceived and Portrayed in Non-European Cultures (translated from the original Dutch by J. Vriend), Grand Rapids, Michigan : William B. Eerdmans Publishing Company, 1 990, pp ix + 1 95